An innovative Au-CdS/ZnS-RGO architecture for efficient photocatalytic hydrogen evolution. Issue 7 (30th January 2018) - Kai, Shuangshuang; Xi, Baojuan; Liu, Xiaolei; Ju, Lin; Wang, Peng; Feng, Zhenyu; Ma, Xiaojian; Xiong, Shenglin
Abstract : An innovative CdS/ZnS-RGO hybrid is synthesized via an one-pot hydrothermal method. The further introduction of Au nanoparticles enables the composite with the merits of heterostructured semiconductor/semiconductor junction benefiting the hole transfer, as well as graphene and noble metal favorable for electron transportation. Abstract : It has been a challenge to design a novel structure for effectively improving the efficiency of charge carriers' separation and transfer. Herein, a CdS/ZnS heterostructure with a tunable Cd/Zn ratio was engineered on reduced graphene oxide (RGO) by a one-pot hydrothermal method followed by in situ formation of Au nanocrystals, which combined the strong electron capture ability of a noble metal and transfer capability of graphene. The CdS/ZnS-RGO architecture was featured by the anisotropic growth of ZnS nanoparticles on a CdS nanorod tip. Relying on the low lattice mismatch, the epitaxial growth of ZnS on CdS as well as CdS on graphene was realized, which rendered the immediate contact of interfaces between different phases. Due to the three features of CdS/ZnS heterostructures, noble metal and graphene being designed together in one material, the Au-CdS/ZnS-RGO heterostructure offered an excellent photocatalytic H2 evolution rate as high as 9.96 mmol h −1 g −1 under visible-light irradiation and photocatalytic stability over 30 h. The results confirmed the efficient separation and transfer of photogenerated electrons and holes.